Non-Isolated n-Stage High Step-up DC-DC Converter for Low Voltage DC Source Integration - Shanthi, T.; Prabha, S. U.; Sundaramoorthy, Kumaravel (IEEE transactions on energy conversion, 2021)
The dc-dc converters with high step-up DC-voltage gain play a vital role in integrating low voltage DC sources. Though several converter topologies are reported in the recent past, attempts have been made to reduce the components, especially the switching devices, passive elements, converter losses, etc., of the converter. A novel DC-DC converter topology, viz., single switched impedance network (SSIN)-based converter with n -stage is proposed in this paper. The operation of the SSIN based converter in continuous and discontinuous conduction modes are discussed. The effect of parasitic elements on DC-voltage gain and efficiency of the SSIN is carried out. The small-signal model of the SSIN converter is derived. The performance of the SSIN converter is compared with the similar converter topologies. The 500 W prototypes of the SSIN with n = 1 and n = 2 are fabricated, and the experimental results are presented in this paper. To improve the converter performance, SiC-based semiconductor devices are used. The SSIN converter with two-stage has low switch loss at 500 W load, improved efficiency during high power and high output voltage operation, the switch stress of V o /2, etc.